PENGARUH PERATURAN PERPAJAKAN, PENGETAHUAN, PEMAHAMAN, SERTA TINGKAT PENGHASILAN TERHADAP KEPATUHAN WAJIB PAJAK - Rahmawati, Aida; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Taxpayer compliance is one of the problems of the implementation of self-assessment system. Therefore, the success of tax collection which has been running by using self-assessment system is determined by the fluctuation level of taxpayer compliance. The purpose of this research is to determine the influence of tax regulation, knowledge and comprehension, as well as income levels toward taxpayer compliance at Tax Office Service (KPP) Pratama Surabaya Sawahan. This research is a quantitative causal research. The population is all individual taxpayers who are registered at the Tax Office Service (KPP) Pratama Sawahan Surabaya. The sample is determined by using purposive sampling method or non-random sample selection, in which the information is obtained by certain consideration. The samples are 61 respondents. The data collection method has been done by issuing questionnaires and the data analysis has been done by using multiple analysis. The result of the research analysis indicates that tax regulation does not give any influence to the taxpayer compliance; knowledge and comprehension gives influence to the taxpayer compliance, and the income level gives influence to the taxpayer compliance.Keywords: Tax regulation, knowledge, comprehension, income level, taxpayer compliance